Decoding Corporate Financial Health: A Comprehensive Quantitative Analysis of Annual Accounts and Financing Strategies - Cut Nadira Putri Kamal (Business and Investment Review, 2024)
Abstract This study navigates the intricate landscape of corporate finance within publicly traded Indonesian companies, aiming to comprehensively grasp their financial health. A holistic approach merges quantitative analyses of annual accounts with qualitative insights from corporate finance, focusing on unraveling the nuanced relationship between financing techniques and financial performance indicators, considering diverse variables such as industry characteristics and company sizes. Employing robust methodologies including regression analysis, correlation analysis, and panel data analysis, the study uncovers significant trends. Noteworthy findings include a burgeoning reliance on debt financing, the emergence of hybrid financing structures, and industry-specific variations in financing preferences. The positive correlation between equity financing and profitability aligns seamlessly with agency theory, underlining its potential for aligning management interests with long-term value creation. Meanwhile, the nuanced impact of debt financing emphasizes the imperative for companies to delicately balance the benefits and risks associated with financial leverage. Implications derived from the research extend practical advice to industry practitioners, emphasizing the need for tailored financing strategies, strengthened corporate governance, and industry-specific considerations. Policymakers are encouraged to play a pivotal role in fostering equity market development, implementing responsible regulatory measures, and championing transparency in financial reporting. This research not only contributes to the existing financial literature by enriching academic discourse but also provides actionable insights for businesses navigating the intricate terrain of corporate finance in Indonesia.